2016
DOI: 10.3390/molecules21121614
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Triterpenoid Saponins in Plants Using Hyphenated Analytical Platforms

Abstract: Abstract:Recently the number of studies investigating triterpenoid saponins has drastically increased due to their diverse and potentially attractive biological activities. Currently the literature contains chemical structures of few hundreds of triterpenoid saponins of plant and animal origin. Triterpenoid saponins consist of a triterpene aglycone with one or more sugar moieties attached to it. However, due to similar physico-chemical properties, isolation and identification of a large diversity of triterpeno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…S7), and this may reflect that it is colocalised with other genes related with resistance to flea beetles. We have previously shown that CYP716s and OSCs are promiscuous enzymes (Khakimov et al, 2015), both with respect to substrate and product specificity, and this may explain how B. vulgaris with a limited number of genes in the pathway may accumulate up to 49 different saponins (Khakimov et al, 2016).…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…S7), and this may reflect that it is colocalised with other genes related with resistance to flea beetles. We have previously shown that CYP716s and OSCs are promiscuous enzymes (Khakimov et al, 2015), both with respect to substrate and product specificity, and this may explain how B. vulgaris with a limited number of genes in the pathway may accumulate up to 49 different saponins (Khakimov et al, 2016).…”
Section: Researchmentioning
confidence: 99%
“…Hederagenin-based saponins are a major deterrent to both diamondback moth and tobacco hornworm Barbarea vulgaris plants accumulate both mono-and bidesmocidic saponins, with between two to five sugars attached to the C-3 or C-28 positions; the corresponding monoglycosides are usually not present (Khakimov et al, 2016). The sapogenins (saponin aglycons) are not active against crucifer herbivores, but only become deterrent when they are 3-O-glucosylated (Nielsen et al, 2010;Augustin et al, 2012).…”
Section: Researchmentioning
confidence: 99%
“…ESI mode, most oleanane type triterpenoid saponins afforded abundant [M-H] -; the adduct process is not reproducible [25]. It has been reported that the [M−H]are the major ions generated in the negative ion mode of UHPLC-ESI-QTOF-MS analyses [23,26].…”
Section: Profiling Of Gotcab Saponins In Gypsophila Glomerata Roots (mentioning
confidence: 99%
“…β-amyrin is a precursor of glycyrrhizin, a triterpenoid saponin found in the roots and stolons of liquorice (Glycyrrhiza glabra) well known for its pharmaceutical properties and as a natural sweetener (Hayashi et al, 2002). β-amyrin is also precursor for the antifungal saponin avenacin A-1 in oat and for the potent insect-feeding deterrent hederagenin glycosides in the Brassicaceae Barbarea vulgaris (Kuzina et al, 2009;Nielsen et al, 2010;Khakimov et al, 2016;Liu et al, 2019);. Additionally, β-amyrin seems to play a role in root development in oat (Kemen et al, 2014) and in Lotus japonicus (Krokida et al, 2013), suggesting that triterpenoids like lupeol and β-amyrin are not exclusively involved in plant defense.…”
Section: Convergent Evolution In Biosynthesis Of Triterpenoid Scaffolmentioning
confidence: 99%
“…Triterpenoid saponin biosynthesis has evolved recurrently in evolution and thus the organization of the genes may not be conserved. In recent years, the Barbarea genus has appeared as a unique plant model as it is the only genus in the agronomically important cabbage family (Brassicaceae) known to accumulate saponins (Khakimov et al, 2016). Some of these saponins (e.g., hederagenin cellobioside) are highly deterrent to Brassica specialist herbivores such as flea beetles (Phyllotreta nemorum) and the diamondback moth (Plutella xylostella) (Kuzina et al, 2009;Kuzina et al, 2011;Liu et al, 2019).…”
Section: Tandem Repeats Of Triterpenoid-biosynthetic Genes and Tritermentioning
confidence: 99%